'It's everything else you do…': Alumni views on extracurricular activities and employability. (July 2015) - Clark, Gordon; Marsden, Rebecca; Whyatt, J Duncan; Thompson, Leanne; Walker, Marion
This article explores students' extracurricular activities and, uniquely, their short- and long-term effects on employability. Drawing on the literature, six research questions are identified. A questionnaire and interviews with alumni provide the quantitative and qualitative information needed. The effects of different extracurricular activities and the skills and qualities they promote are demonstrated for early- and later-career jobs, as are the complementary effects for employability of degree schemes and extracurricular activities. Alumni who are now recruiters of staff use their double perspective to explain the role extracurricular activities have played in their lives and now as professional recruiters. This article shows how the alumni of any university could share these insights with undergraduates.